DYNAMIQUE DU CLIMAT ET IMPACT SUR LA PRODUCTION D’ORGE DANS LA ZONE DE BÉJA AU NORD-OUEST DE LA TUNISIE - Mansouri, Sonia; Radhouane, Leila (European Scientific Journal, ESJ, 2015)
This study aims to evaluate the effects of climate change on barley production in the Beja region in north western Tunisia. Precipitation and temperature are among the most critical factors that influence agricultural sector. The results showed that the average annual precipitation has increased. It was also shown that the distribution of rainfall has changed significantly. In fact, February rain is more than doubled; while the June precipitation is diminished. For temperature, it was seen an increase in average temperatures due to the increase in minimum temperatures. The trend of barley production appears stable and even slightly positive. This improved yields of barley appear related primarily to the increase in average temperatures (especially minimum) and secondly to rainfall increase.